2017
DOI: 10.15446/acag.v66n4.63597
|View full text |Cite
|
Sign up to set email alerts
|

Asymbiotic seed germination and in vitro propagation of Cattleya trianae Linden & Reichb.f. (Orchidaceae)

Abstract: Cattleya trianae (Linden & Reichb.f., 1860), Colombian national flower, is in danger of extinction due to the destruction of its natural habitats and excessive collection for horticultural purposes. Therefore, in vitro culture is a tool for the conservation of threatened species. In this study we determined the most suitable culture medium for asimbytic seed germination and in vitro propagation of C. trianae. Initially, mature capsules were collected, the seeds were subsequently disinfected and seeded with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 13 publications
0
7
0
4
Order By: Relevance
“…In this study, the better percentage of germination (9.3%) was obtained in the Phytamax™ medium with 30% of its basal salts, added with banana puree as an organic supplement, which represents a much lower cost in the acquisition of inputs and allows greater accessibility to reproduce this species. The addition of organic supplements to the culture media improves the development and lower production costs of orchids (Moreno and Menchaca, 2007;Pakum et al, 2016;Salazar and Vega, 2017). In general, it has been reported that adding banana to the growing media improves the development of the plant and the roots (Azlan et al, 2016;Menezes et al, 2016;Wida and Hariyanto, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the better percentage of germination (9.3%) was obtained in the Phytamax™ medium with 30% of its basal salts, added with banana puree as an organic supplement, which represents a much lower cost in the acquisition of inputs and allows greater accessibility to reproduce this species. The addition of organic supplements to the culture media improves the development and lower production costs of orchids (Moreno and Menchaca, 2007;Pakum et al, 2016;Salazar and Vega, 2017). In general, it has been reported that adding banana to the growing media improves the development of the plant and the roots (Azlan et al, 2016;Menezes et al, 2016;Wida and Hariyanto, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, se utilizó un control que consistió en la no aplicación de pretratamiento (Benítez et al, 2013). Para esto, se implementó el método de jeringuilla descrito por Salazar (2012): un grupo de semillas se colocó dentro de una jeringa de 5 mL, equipada con un ltro de tela (Salazar & Vega, 2017); al nal del periodo de pre-tratamientos se realizaron tres enjuagues con agua destilada para eliminar los sobrantes de la solución de cloro. Se utilizaron 5 réplicas de 100 semillas, a las cuales se les adicionó 5 mL de la solución de TZ a tres concentraciones (0,25 %, 0,15 % y 0,1 %), y tres tiempos de exposición (6 h, 12 h y 24 h), a una temperatura de 25 °C, en condiciones de oscuridad.…”
Section: Pretratamiento Y Viabilidad De Semillasunclassified
“…Por lo regular, las semillas con capas duras necesitan ser escaricadas y, para llevar a cabo este proceso, suele utilizarse el NaClO con el propósito de mejorar la efectividad de la tinción (Salazar & Vega, 2017). En semillas de Cypripedium lentiginosum P.J.…”
Section: Comparación De Germinación Y Viabilidadunclassified
“…Asimismo, funciona como un apoyo para tomar decisiones estratégicas con respecto a la selección de conjuntos de semillas de alta calidad, esperando satisfacer los requerimientos del consumidor (Filho, 2015). La prueba de tetrazolio es ideal para determinar la capacidad germinativa (viabilidad) de una semilla, siendo exitosa en gran variedad de especies cultivables (Salazar y Vega, 2017;Salazar y Botello, 2018;Salazar, Maldonado y Quintero, 2018;Salazar, Quintero, J y Rojas, 2020;Paiva, Torres, Almeida, Da Silva y Torquato, 2017). Esta prueba es una importante herramienta por su rápida y certera estimación de la viabilidad y vigor en la semilla, permitiendo obtener resultados en corto tiempo (Días y Alves, 2008).…”
Section: Introductionunclassified